2019
DOI: 10.17576/jsm-2019-4804-15
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties and Toxicity Assessment of the Crescentia cujete Extracts in Brine Shrimp (Artemia salina)

Abstract: Crescentia cujete has traditionally been used to treat various ailments. The present study attempted to determine the antioxidant activities of 100% ethanol, 50% ethanol and aqueous extracts of the leaves, bark and fruit of the herb. Additionally, the toxicity of the extracts was investigated in brine shrimp. The results showed that 100% ethanol leaf extract had the highest antioxidant activity with an IC 50 value of 261.97 ± 0.57 μg/mL according to the 2,2-diphenyl-1picrylhydrazil (DPPH) radical scavenging as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…The various pharmacological properties of C. cujete includes antioxidant [ 8 , 10 , 40 ], antidiabetic [ 37 , 46 , 47 ], anti-inflammatory [ 48 ], anthelmintic [ 13 ], antibacterial [ 7 , 10 , 31 , 34 , 48 , 49 ], antimycobacterial [ 50 ], anticholesterol [ 13 ], antivenom [ 51 ], wound healing [ 9 ], safety potentials, cytotoxic [ 10 , 13 , 38 , 51 ], acaricidal [ 29 ], neuroprotection [ 52 ], and antiangiogenic [ 53 ] ( Table 3 ). Additionally, the antioxidant, antibacterial, and anticancer activities of four ( Nigrospora sphaerica , Fusarium oxysporum , Gibberella moniliformis , and Beauveria bassiana ) isolated endophytic fungi from the plant had been reported [ 55 ].…”
Section: Pharmacological Potentialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The various pharmacological properties of C. cujete includes antioxidant [ 8 , 10 , 40 ], antidiabetic [ 37 , 46 , 47 ], anti-inflammatory [ 48 ], anthelmintic [ 13 ], antibacterial [ 7 , 10 , 31 , 34 , 48 , 49 ], antimycobacterial [ 50 ], anticholesterol [ 13 ], antivenom [ 51 ], wound healing [ 9 ], safety potentials, cytotoxic [ 10 , 13 , 38 , 51 ], acaricidal [ 29 ], neuroprotection [ 52 ], and antiangiogenic [ 53 ] ( Table 3 ). Additionally, the antioxidant, antibacterial, and anticancer activities of four ( Nigrospora sphaerica , Fusarium oxysporum , Gibberella moniliformis , and Beauveria bassiana ) isolated endophytic fungi from the plant had been reported [ 55 ].…”
Section: Pharmacological Potentialsmentioning
confidence: 99%
“…Going by this report, it was observed that all extracts are bioactive and toxic to the cells, since LC 50 values were lower than 1000 ppm based on Meyer's toxicity index. Sagrin et al [ 10 ], in a related and recent study from Malaysia, similarly determined the cytotoxic effects of leaves, bark, and fruits extracts (CE, aqueous-ethanol, and aqueous) in BSLT using potassium dichromate dissolved in artificial seawater as control. The concentrations tested are 1.953, 3.907, 7.813, 15.625, 31.25, 62.50, 125, 250, 500, and 1000 μ g/mL.…”
Section: Pharmacological Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidants mainly comprise of both enzymes and non-enzymes, which include glutathione peroxidase, catalase, vitamins, and polyphenols. Plants, especially tropical fruits, have been identified as important sources of polyphenols (Sagrin et al, 2019;Gülçin, 2020). In fact, several medicinal drugs are derived from active ingredients in plants (Fabricant and Farnsworth, 2001).…”
Section: Introductionmentioning
confidence: 99%